EDUKASI STRETCHING METODE PNF BAGI ATLET DISABILITAS INTELEKTUAL SPECIAL OLYMPICS INDONESIA DKI JAKARTA - Slamet Sukriadi; Muhamad Arif; Bazuri Fadillah (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
AbstractCoaching for Intellectual athletes with disabilities Special Olympics DKI Jakarta aims to  improve sports skills and also has an impact on the ability of physical components including  flexibility so that athletes are not prone to injury from the training process carried out.  However, the obstacle in the coaching is that not all coaches and parents understand and  consider the importance of stretching exercises, especially exercises with the PNF method that  have not been carried out optimally. Based on the situation analysis, the partner problem  education that will be carried out in this community service is PNF method stretching education  for athletes with Intellectual Disabilities Special Olympics Indonesia DKI Jakarta. By  providing this education, it can help coaches and parents to create good and useful stretching  exercise programs for athletes. In this PKM activity, the main priority will be to provide  education about stretching the PNF (Propioceptive Neuromuscular Facilitation) method. The  method in this activity is education that is in accordance with the analysis of the situation and  the needs of the target. This Community Service Implementation Program was carried out in 5  Special Olympics Indonesia Special Olympics Development Centers DKI Jakarta during the 1 year process.  AbstrakPembinaan Sepanjang Tahun bagi atlet Inteletual disabilitas Special Olympics DKI Jakarta  bertujuan untuk meningkatkan keterampilan cabang olahraga dan juga berdampak pada  kemampuan komponen fisik termasuk fleksibilitas sehingga, atlet tidak rentan cidera dari  proses latihan yang dilakukan. Namun yang menjadi kendala dalam pembinaan tersebut adalah  tidak semua pelatih dan orang tua mengerti dan faham serta menganggap penting latihan  peregangan terutama latihan dengan metode PNF yang belum dilaksanakan secara optimal.  Berdasarkan analisis situasi maka Edukasi permasalahan mitra yang akan di laksanakan dalam  pengabdian masyarakat ini adalah edukasi stretching metode PNF bagi atlet Disabilitas  Intelektual Special Olympics Indonesia DKI Jakarta. Dengan diberikannya edukasi ini dapat  membantu Pelatih dan orang tua, untuk membuat program latihan peregangan (stretching) yang  baik dan bermanfaat untuk atlet. Dalam kegiatan pengabdian ini yang akan di jadikan prioritas  utama adalah memberikan Edukasi tentang stretching metode PNF (Propioceptive  Neuromuscular Facilitation). Metode yang dipakai dalam kegiatan ini adalah edukasi yang disesuaikan dengan analisis situasi dan kebutuhan khalayak sasaran stategis. Program  Pelaksanaan Pengabdian kepada Masyarakat ini di laksanakan di 5 Wilayah Sentra Pembinaan  Special Olympics Indonesia DKI Jakarta, dengan proses 1 tahun